If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -9x = 3x + -70 Reorder the terms: 14 + -9x = -70 + 3x Solving 14 + -9x = -70 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 14 + -9x + -3x = -70 + 3x + -3x Combine like terms: -9x + -3x = -12x 14 + -12x = -70 + 3x + -3x Combine like terms: 3x + -3x = 0 14 + -12x = -70 + 0 14 + -12x = -70 Add '-14' to each side of the equation. 14 + -14 + -12x = -70 + -14 Combine like terms: 14 + -14 = 0 0 + -12x = -70 + -14 -12x = -70 + -14 Combine like terms: -70 + -14 = -84 -12x = -84 Divide each side by '-12'. x = 7 Simplifying x = 7
| 6x+1=26-2x | | 10x+5y=-15 | | -4(2x-10)+3=-10 | | 7(6x-3)=29 | | a^2+7ab+10b^2= | | b^3+49b= | | 10-2w=-12 | | 10-2w=12 | | 7x^2+2x-9=0 | | 2x+13=9x-8 | | 9a+4a=8a | | 4x-1=11x-42 | | 2x+22=10x-42 | | -10x+15=5x-30 | | -7(t-3)+4t=-3(-7+t) | | (-6)-5= | | (7)(-4)= | | 2x+5=7x-20 | | 2q-4+8q=7q-8+3q | | r+11+8r=11 | | (xy-420)=3x-y | | 7X-(3+2x)=X+9 | | 6(xy-420)=0 | | S=p+prt | | 3h-11=-21 | | 6(xy-420)=3x-y | | Y=-4x-7 | | 7-2(4x-5)=-5x+11 | | 3(X+5)=7-5X | | 7(3-2X)=15(1-X) | | 26-2y=8Y-44 | | 4x-3(x+5)=1-4x |